(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Aphthritis, commonly referred to as canker sores, is a multifactorial condition that affects the oral mucosa, causing discomfort and impacting quality of life. This article explores the causes of aphthritis, providing a comprehensive analysis of genetic, environmental, immunological, and microbiological factors. By synthesizing current research, this study offers insights into the disease’s origins and suggests avenues for prevention and management.